A compact printed multistubs loaded resonator rectangular monopole antenna design for multiband wireless systems. Issue 9 (11th July 2017) - Kumar, Ashok; Jhanwar, Deepak; Sharma, Mahendra Mohan
Abstract: In the present article, a compact triple‐band multistubs loaded resonator printed monopole antenna is proposed. The antenna consists of a quarter wavelength two asymmetrical inverted L‐shaped stubs to excite two resonant modes for 3.5/5.5 GHz bands and one integrated horizontally T‐shaped stub with inverted long L‐shaped stub to excite resonant mode for 2.5 GHz band. By loading these stub resonators along y‐axis with distinct gaps, the antenna resonates at three frequencies 2.57/3.52/5.51 GHz covering the desired bands while keeping compact size of 24 × 30 mm 2 (0.2 λ 0 × 0.25 λ 0 ). The proposed antenna is fabricated on Rogers RT/duroid 5880 substrate with thickness 0.79 mm and its performance experimentally verified. The measured results reveal that the antenna has the impedance bandwidths of about 210 MHz (2.50‐2.71 GHz), 260 MHz (3.37‐3.63 GHz), and 650 MHz (5.20‐5.85 GHz), for 2.5/3.5/5.5 GHz WiMAX and 5.2/5.8 GHz WLAN band systems. The antenna provides omnidirectional radiation patterns and flat antenna gains over the three operating bands. In addition, the design approach and effects of multistubs resonator lengths on the operating bands are also examined and discussed in detail.